El modelo probabilístico: características y modelos derivados - Vilares, Jesús (Revista General de Información y Documentación, 2009)
A review of the art of the family of probabilistic model of information retrieval is presented. Based on its basic priciples, difefferent specific models are analysed: the BIR model –the most basic one– the classic BM25 and the DFR models, one of the last developed.